A case report of fibrolamellar hepatocellular carcinoma, with particular reference to preoperative diagnosis, value of molecular genetic diagnosis, and cell origin - Atsushi Takahashi; Hiroshi Imamura; Ryota Ito; Fumihiro Kawano; Yu Gyoda; Hirofumi Ichida; Ryuji Yoshioka; Yoshihiro Mise; Yuki Fukumura; Katsuhiro Sano; Akio Saiura (Surgical Case Reports)
Abstract Background Fibrolamellar hepatocellular carcinoma (FL-HCC) is a liver tumor that occurs almost exclusively in young adults without underlying liver disease. In spite of its distinct clinical characteristics and specific imaging findings, preoperative diagnosis is often difficult due to the extremely low incidence of the tumor. Although FL-HCC shows particular morphological features on H&E-stained tissue sections, differential diagnosis from ordinary HCC, especially the scirrhous variant of HCC, and intrahepatic cholangiocarcinoma needs additional immunohistochemical (IHC) analyses and/or molecular genetic testing. Case presentation A 21-year-old male patient was referred to our hospital for further evaluation of a large liver mass. Abdominal ultrasound examination, contrast-enhanced computed tomography, and magnetic resonance imaging revealed a well-defined hypervascular lobulated liver mass, 11 × 11 cm in diameter, with a central scar and calcification, in segments 5/8. Under the diagnosis of FL-HCC, we carried out extended anterior sectorectomy, including a part of segment 4. On microscopic examination, the tumor was composed of proliferating polygonal cells with abundant eosinophilic granular cytoplasm containing nuclei with vesicular chromatin and enlarged nucleoli, in an abundant stroma. Collagen fibers arranged in a parallel lamellar pattern were seen in the tumor stroma. These findings, together with the results of subsequent IHC analyses using HAS, CK7, and CD 67, we made the diagnosis of FL-HCC, which was further confirmed by detection of the DNAJB1-PRKACA fusion gene in the tumor cells by RT-PCR. Conclusion FL-HCC shows distinct imaging appearances. Although it also has characteristic morphological features, combined use of IHC and/or molecular genetic studies are necessary for the final diagnosis.